The scaling of colony size with nest volume in termites: A role in population dynamics? - Lima Pequeno, Pedro A C; Franklin, E.; Venticinque, Eduardo Martins; Serrão Acioli, Agno N. (Ecological Entomology, 2013)
Colony size is often attributed a key role in social insect population ecology. However, in nest-building termites, colony size is a power function of nest volume, so that colonies of species with low scaling exponents tend to grow less as their nests are expanded. Thus, in such species, intercolonial differences in colony size may be less likely to develop, and changes in species total biomass may largely reflect those in colony numbers rather than colony sizes. The scaling of colony biomass with nest volume in three termite species, namely Anoplotermes banksiEmerson, Neocapritermes braziliensis Snyder and Labiotermes labralis Holmgren was determined. Then, their nests were counted and their total biomass in plots across an Amazonian rainforest landscape was estimated. Finally, whether the strength of the relationship between total biomass and number of nests reflected species scaling exponents was examined. Scaling exponents were 0.47 for N. braziliensis, 0.57 for A. banksi, and 0.83 for L. labralis. On the other hand, the strength of the relationship between total biomass and the number of nests (r2) followed the opposite trend: 0.93 for N. braziliensis, 0.92 for A. banksi, and 0.53 for L. labralis. It is suggested that the scaling of colony size with nest volume may mediate termite population dynamics: as the scaling exponent decreases across species, changes in total biomass would increasingly reflect changes in colony numbers, with an accompanying increase in the importance of colony births and deaths as opposed to colony growth. © 2013 The Royal Entomological Society.
Keywords: Abundance; Allometry; Biomass; Colony; Nest; Population Dynamics; Population Ecology; Rainforest; Social Insect; Termite; Anoplotermes; Hexapoda; Isoptera; Neocapritermes; Termitidae